De Novo Assembly and Comparative Transcriptome Analysis Provide Insight into Lysine Biosynthesis in Toona sinensis Roem. (7th June 2016) - Zhang, Xia; Song, Zhenqiao; Liu, Tian; Guo, Linlin; Li, Xingfeng
Abstract : Toona sinensis Roem is a popular leafy vegetable in Chinese cuisine and is also used as a traditional Chinese medicine. In this study, leaf samples were collected from the same plant on two development stages and then used for high-throughput Illumina RNA-sequencing (RNA-Seq). 125, 884 transcripts and 54, 628 unigenes were obtained through de novo assembly. A total of 25, 570 could be annotated with known biological functions, which indicated that the T. sinensis leaves and shoots were undergoing multiple developmental processes especially for active metabolic processes. Analysis of differentially expressed unigenes between the two libraries showed that the lysine biosynthesis was an enriched KEGG pathway, and candidate genes involved in the lysine biosynthesis pathway in T. sinensis leaves and shoots were identified. Our results provide a primary analysis of the gene expression files of T. sinensis leaf and shoot on different development stages and afford a valuable resource for genetic and genomic research on plant lysine biosynthesis.